Polyglucosan bodies in intramuscular nerve branches are a poor predictor of GBE1 mutation and adult polyglucosan body disease. Issue 3 (March 2016) - Furtado, Larissa V.; Kadri, Sabah; Wurst, Michelle N.; Long, Bradley C.; Segal, Jeremy P.; Pytel, Peter
ABSTRACT: Introduction: Adult polyglucosan body disease (APBD) is associated with formation of polyglucosan bodies in peripheral nerve branches. Some muscle biopsies show these inclusions in intramuscular nerve branches. It has not been established whether the presence of multiple polyglucosan bodies in intramuscular peripheral nerve branches could or should suggest testing for APBD. Methods: Fifteen muscle biopsies from adults between the ages of 36 and 84 years, all showing polyglucosan bodies in intramuscular peripheral nerve twigs, were tested by sequencing of the GBE1 gene. Results: In 4 patients, testing identified heterozygous missense mutations not previously described. No homozygous or compound heterozygous mutations were identified. Conclusions: The presence of polyglucosan bodies in intramuscular nerve twigs by itself, even if they are multiple, is not an indication of APBD. Further testing may only be indicated in patients with clinical disease manifestations. Muscle Nerve 53: 473–475, 2016